MICROENCAPSULATION OF INDIGENOUS POULTRY LACTIC ACID BACTERIA PROBIOTIC ON THE COMPETITIVE EXCLUSION AGAINST Salmonella enteritidis AND Escherichia coli IN VITRO - Monica Sonia Indri Pradipta; Sri Harimurti; Widodo Hadisaputro (Buletin Peternakan, 2017)
This study was conducted to investigate the effect of microencapsulation of lactic acid bacteria (LAB) probiotic isolated from chickens’ gastrointestinal tract on Salmonella enterica serotype enteritidis ATCC 13076 and Escherichia coli EPEC. Probiotic of LAB used were Streptococcus thermophilus strain Kp-2, Lactobacillus murinus strain Ar-3, and Pediococcus acidilactici strain Kd-6. Microencapsulation were conducted by spray drying with inlet/outlet temperatures of 160/80°C using maltodextrin and skim milk powder (20% w/v) as coating materials. Competitive exclusion test was conducted in vitro using well diffusion method. Variable measured in this study was the clear zone observed. The data of clear zone among treatments were analyzed using analysis of variance (ANOVA) one way followed by Duncan multiple range test (DMRT); except the data of clear zone resulted by probiotic before and after microencapsulation that was analyzed using t-test. The result showed that the ability of each strain against pathogen was decreased after being encapsulated. S. thermophilus before and after microencapsulation had the same antagonistic ability against E. coli and S. enteritidis (P>0.05). Microencapsulation process with spray drying method decreased antagonistic ability of probiotic against pathogenic bacteria both in single and multi strain.